Analysis of Community Knowledge, Practices, and Perceptions Regarding the Management of Leftover, Damaged, and Expired Medicines in Tegal Sari Village - Azzahra, Nia; Wati, Indhika Tyas; Pranata, Yovi; Muliana, Hilda; Sabda Wahab (JUKEJ : Jurnal Kesehatan Jompa, 2025)
Medicines play an important role in maintaining and restoring public health. However, limited knowledge and improper management can cause various problems, such as the accumulation of leftover medicines, the use of expired medicines, and the disposal of medicines that does not comply with regulations. This study aims to evaluate the level of knowledge, actions, and perceptions of the community regarding the management of leftover, damaged, and expired medicines in Tegal Sari Village, Belitang II District, East Ogan Komering Ulu Regency in 2025. This study used a quantitative analytical design with a cross-sectional approach. A total of 86 respondents were selected using purposive sampling. The research instrument was a structured questionnaire that assessed the level of knowledge, actions, and perceptions of the community. Data analysis was performed descriptively and analytically using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the relationship between variables. The study showed a significant relationship between the variables of knowledge, actions, and perceptions of the community regarding the management of leftover, damaged, and expired medicines in Tegal Sari Village in 2025 with a p-value <0.05. Conclusion there is a significant relationship between knowledge, actions, and public perception and the management of leftover, damaged, and expired medicines in Tegal Sari Village. Although the respondents' knowledge and actions were in the good category, medicine management practices were still not fully in accordance with standards. Educational interventions and the provision of medicine disposal facilities are needed to improve safe medicine management behavior.